Flexural Performance of RC Beams Strengthened with Pre-Stressed Iron-Based Shape Memory Alloy (Fe-SMA) Bars: Numerical Study - Ahmed Khalil; Mohamed Elkafrawy; Wael Abuzaid; Rami Hawileh; Mohammad AlHamaydeh (Buildings, 2022)
The iron-based shape memory alloy (Fe-SMA) has promising applications in strengthening and repairing aged steel-reinforced concrete structural elements. Fe-SMA bars can produce pre-stressing forces on reinforced concrete members by activating their shape memory phenomenon upon heating. This study aims to numerically evaluate the impact of pre-stressed Fe-SMA bars on the structural behavior of reinforced concrete (RC) beams at the serviceability and ultimate stages. Nonlinear finite element (FE) models were developed to predict the response of RC beams externally strengthened with Fe-SMAs. The model shows to correlate well with published experimental results. A parametric investigation was also carried out to examine the effect of various concrete grades, pre-stressing levels, and Fe-SMA bars’ diameter on load-deflection behavior. In light of the innovative nature of the Fe-SMA strengthening technique, a comparison investigation was established between RC beams strengthened with Fe-SMA bars against different pre-stressing systems, such as carbon fiber reinforced polymer (CFRP) bars, glass fiber reinforced polymer (GFRP) bars, and steel strands. The numerical findings showed a significant increase in the beams’ load-carrying capacity with larger Fe-SMA bars’ diameter. Specifically, using 12 mm Fe-SMA bars instead of 6 mm increased the beam’s strength by 73%. However, a 14% reduction in ductility was recorded for that case. Moreover, the pre-stressing level of Fe-SMA bars and concrete grade showed a negligible effect on the ultimate strength of the examined beams. Moreover, increasing the pre-stressing level and concrete strength significantly enhanced the load-deflection response in the serviceability stage. Furthermore, using 2T22 mm of Fe-SMA bars resulted in a better structural performance of RC beams compared to other techniques with 2T12 mm, with a comparable cost. Thus, it can be concluded that using Fe-SMA bars embedded in a shotcrete layer attached to the beam’s soffit is a viable and promising strengthening strategy. Nevertheless, further experimental investigations are recommended to further ascertain the reported findings of this numerical investigation.